Exploring the Role of Social Media Marketing in Shaping Purchasing Intentions for T-shirts in Sri Lanka (Vallis Aurea, 2023)
This research investigates the impact of social media marketing on consumers' purchasing intention in Sri Lanka's T-shirt industry. It examines factors such as Informativeness, Trendiness, Interactivity, Personalization, and Word-of-Mouth (WOM) in relation to T-shirt purchases.The study uses a quantitative approach, surveying 351 individuals in Colombo District who use social media. A structured questionnaire collects data on demographics, social media marketing factors, and purchasing intention.Data cleaning ensures accuracy, employing Cronbach's Alpha coefficients for reliability testing. Correlation and linear regression analyses reveal that social media marketing significantly influences purchasing intention, explaining 19.8% of the variance.This research offers empirical evidence for the impact of social media marketing in a specific industry and location, highlighting its relevance for T-shirt businesses in Sri Lanka. It also suggests avenues for further research.